Outbreak of cryptosporidiosis in sea caged turbot (Psetta maxima) - Fioravanti, Maria Letizia; Quaglio, F.; Caffara, Monica; Gustinelli, A.; Palenzuela, Oswaldo; Krizanac, S.; Colak, S. (2015)
Comunicación presentada en 17th International Conference on Diseases of Fish and Shellfish, celebrada en Las Palmas, España, del 7 al 11 de septiembre de 2015 Turbot (Psetta maxima) is currently one of the most promising species for European mariculture but although most of the critical aspects threatening production have been optimized, transmissible diseases may still represent a limiting factor. In Autumn 2014 two batches of 5 turbot (mean weight 305g) caged in northern Adriatic Sea and showing melanosis, exophthalmos and skin/fin lesions were subjected to bacteriological and parasitological examination. In addition, visceral organs of twenty fish from the same two cages were fixed directly on the field in 10% buffered formalin. Necropsy showed in all specimens pale-yellow liver and intestinal distension with abundant mucous contents. From the fish owing to one batch ascites was also observed and Vibrio scophthalmi was isolated at the bacteriological exam. Routine parasitological examination did not reveal parasites in any organs except for the intestines, where developmental stages of unidentified parasites were observed. In order to identify the parasite, portions of intestine from all fish were subjected to DNA extraction followed by amplification of 18S rDNA portions. BLAST search of the sequences permitted to ascribe the parasites to the genus Cryptosporidium. In the histopathological study, a mild-to-severe infection by cryptosporidia was detected in the intestine of all fish from both cages. Epicytoplasmic stages of parasites lining the luminal surface of the epithelial cells were observed, generally with the presence of intra-epithelial sporogonic stages located deeply within the enterocytes layer. In some areas, oocysts were present within vacuolated areas in the mucosa, with diffuse necrosis, sloughing off the epithelium and loss of the enterocytes brush border; lamina propria and submucosa were oedematous. Inflammatory response involving mainly lymphocytes and, in heavy infections, rodlet cells ...